Attitudes to out-of-programme experiences, research and academic training of gastroenterology trainees between 2007 and 2016. Issue 1 (19th June 2018) - McFarlane, Michael; Bhala, Neeraj; China, Louise; Alrubaiy, Laith; Chedgy, Fergus; Disney, Benjamin R; Farmer, Adam D; Fogden, Edward; Sadler, Gareth; Hull, Mark A; McLaughlin, John; Ellison, Howard; et al.
Abstract : Objective: Academic medical training was overhauled in 2005 after the Walport report and Modernising Medical Careers to create a more attractive and transparent training pathway. In 2007 and 2016, national web-based surveys of gastroenterology trainees were undertaken to determine experiences, perceptions of and perceived barriers to out-of-programme research experience (OOP-R). Design, setting and patients: Prospective, national web-based surveys of UK gastroenterology trainees in 2007 and 2016. Main outcome measure: Attitudes to OOP-R of two cohorts of gastroenterology trainees. Results: Response rates were lower in 2016 (25.8% vs 56.7%) (p<0.0001), although female trainees' response rates increased (from 28.8% to 37.6%) (p=0.17), along with higher numbers of academic trainees. Over 80% of trainees planned to undertake OOP-R in both surveys, with >50% having already undertaken it. Doctor of Philosophy/medical doctorate remained the most popular OOP-R in both cohorts. Successful fellowship applications increased in 2016, and evidence of gender inequality in 2007 was no longer evident in 2016. In the 2016 cohort, 91.1% (n=144) felt the development of trainee-led research networks was important, with 74.7% (n=118) keen to get involved. Conclusions: The majority of gastroenterology trainees who responded expressed a desire to undertake OOP-R, and participation rates in OOP-R remain high. Despite smaller absolute numbers responding than in 2007, 2016 trainees achieved higher successful fellowship application rates. Reassuringly more trainees in 2016 felt that OOP-R would be important in the future. Efforts are needed to tackle potential barriers to OOP-R and support trainees to pursue research-active careers.